Enhancing Boardroom Diversity in Saudi Arabia - Abdullah Eskandarany (De Gruyter, 2023)
This book reviews Saudi boardroom diversity of listed companies with regard to age, gender, nationality, experience and educational profile data of board members. It summarizes Saudi corporate governance legislation from 2006 to 2020 and the socio-cultural history and barriers to diversity, to produce a comprehensive picture for academics and practitioners and identify strategies to increase boardroom diversity in this developing, major economy.
Keywords: 650; Boardroom Diversity; Corporate Governance; Board Diversity; Effectiveness; Saudi Listed Companies; Corporate Board.